2020
DOI: 10.3390/ijms21228477
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting Aggravates Lupus Nephritis through Increasing Survival and Autophagy of Antibody Secreting Cells in MRL/lpr Mice

Abstract: Systemic lupus erythematosus (SLE) is an autoimmune disease in which the main contributors to organ damage are antibodies against autoantigens, such as double-stranded DNA (dsDNA). Calorie restriction and intermittent fasting (IF) have been shown to improve autoimmune disease symptoms in patients and animal models. Here, we tested the hypothesis that IF might improve symptoms in MRL/lpr mice, which spontaneously develop an SLE-like disease. Groups of mice were fed every other day (IF) or provided food ad libit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…In addition, ADF did not significantly alter the mRNA level of BAFF, a factor critical for the maturation and survival of B cells in the SMGs, and did not affect the production of antinuclear and anti-M3R autoantibodies, indicating that the protective role of ADF in sialadenitis in NOD mice is not associated with the reduced autoantibody-secreting activities of B cells. Despite the profound and widely reported immunoregulatory effects of intermittent fasting [22][23][24][25][26], one recent study showed that MRL/lpr lupus-prone mice with intermittent fasting exhibited enhanced B cell activity and autoantibody production, and an exacerbated severity of nephritis [31]. The different impacts of intermittent fasting on B cell activity and function are probably attributed to distinct disease contexts, which awaits future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ADF did not significantly alter the mRNA level of BAFF, a factor critical for the maturation and survival of B cells in the SMGs, and did not affect the production of antinuclear and anti-M3R autoantibodies, indicating that the protective role of ADF in sialadenitis in NOD mice is not associated with the reduced autoantibody-secreting activities of B cells. Despite the profound and widely reported immunoregulatory effects of intermittent fasting [22][23][24][25][26], one recent study showed that MRL/lpr lupus-prone mice with intermittent fasting exhibited enhanced B cell activity and autoantibody production, and an exacerbated severity of nephritis [31]. The different impacts of intermittent fasting on B cell activity and function are probably attributed to distinct disease contexts, which awaits future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The two predominant patterns of IF include: (1) time-restricted feeding, which contains three variants—16/8, 18/6, and 20/4—16/8 consists of a 16 h fast followed by an 8 h eating period, 18/6 consists of fasting for 18 h followed by 6 h eating, and 20/4 consists of fasting for 20 h followed by 4 h eating [ 8 ]; and (2) alternating 24 h fasting with 24 h feeding, and the 5/2 or 4/3 systems, in which one eats for 5 days of the week and fasts for 2 days, or eats for 4 days and fasts for 3 days [ 8 ] ( Figure 1 ). Recently, IF has also been shown to modulate systemic metabolic status through multiple mechanisms, thereby delaying the progression of various diseases, such as cardiovascular [ 9 , 10 ], neurological [ 11 , 12 ], and autoimmune [ 13 , 14 , 15 ] diseases. The role of IF in diabetic nephropathy (DN), a metabolic disorder, is now being investigated in depth.…”
Section: Introductionmentioning
confidence: 99%